Recent Climate Change and its Influence on Vegetation Cover in Northern Wadi Araba, Jordan - Al-Aroud, Ibrahim; Bilbeisi, Hisham; Ghonmyeen, Tareq (Jordan Journal of Social Sciences, 2020)
Climate change is expected to have serious adverse effects on water resources, the ecosystem and the economic activities, particularly in marginal areas where precipitation is limited. General Circulation Global Models project that the eastern Mediterranean, which already suffers from serious resources challenges will experience a drop in annual precipitation and a concomitant rise in air temperature following the buildup of Greenhouse gases in the atmosphere. This climate change will have debilitating consequences on the water resources and the ecosystem in Jordan, given its marginal climate regime, its limited renewable water resources and the swelling population. The present paper assesses the climate trend in the northern Wadi Araba basin, southwestern Jordan, which comprises a wide differentiation of climates and natural habitats. Time series of near surface annual air temperature and total annual precipitation were examined using linear regression. Monthly soil moisture and the Palmer Drought Severity Index (PDSI) were also calculated to establish any agricultural drought trend during the past half century. Five satellite images spanning the period 1987 through 2015 were integrated to track changes in land cover for areas situated above the 300 m contour line. Results show that annual air temperature increased by 2.7 oC, and total annual precipitation dropped by about 100 mm (>30%) between 1971 and 2016. The PDSI has increased and soil moisture within the top meter declined significantly, particularly after 1999. Analysis of the satellite images reveals that barren lands swelled at the expense of rain-fed agriculture, forests and grazing lands. Barren lands increased by ~150% between 2002 and 2015, with a concurrent decline of the other land covers. Persistence of this trend will have devastating corollary effects on water resources, the economic activities and the natural habitats in the study area. As a consequence of this recent climate change, there has been a frequent failure of rain-fed agriculture, and the discharge of numerous water springs within the study area started to either dwindle or ceased to exist.